The development of the Kedah state library corporation : Ismail Hussein Collection - Zainol Rashid, Zahidi (Persatuan Pustakawan Malaysia, 2011)
The Kedah State Library Corporation aims to establish libraries in all the 11 districts in Kedah. Apart from serving the community, the Corporation also establishes special collections of local scholars. This article traces the setting-up of the Ismail Hussein Collection